A Culture-Proven Case of Community-Acquired Legionella Pneumonia Apparently Classified as Nosocomial: Diagnostic and Public Health Implications - Annalisa Bargellini; Isabella Marchesi; Patrizia Marchegiano; Luca Richeldi; Roberto Cagarelli; Greta Ferranti; Paola Borella (Case Reports in Medicine)
We report a case of Legionella pneumonia in a 78-year-old patient affected by cerebellar haemangioblastoma continuously hospitalised for 24 days prior to the onset of overt symptoms. According to the established case definition, this woman should have been definitely classified as a nosocomial case (patient spending all of the ten days in hospital before onset of symptoms). Water samples from the oncology ward were negative, notably the patient’s room and the oxygen bubbler, and the revision of the case history induced us to verify possible contamination in water samples collected at home. We found that the clinical strain had identical rep-PCR fingerprint of L. pneumophila serogroup 1 isolated at home. The description of this culture-proven case of Legionnaires’ disease has major clinical, legal, and public health consequences as the complexity of hospitalised patients poses limitations to the rule-of-thumb surveillance definition of nosocomial pneumonia based on 2–10-day incubation period.